Caffeine does not augment markers of muscle damage or leukocytosis following resistance exercise - Machado, M.; Koch, A. J.; Willardson, J. M.; dos Santos, F. C.; Curty, V. M.; Pereira, L. N. (International Journal of Sports Physiology and Performance, 2010)
Purpose: The purpose of this study was to evaluate the effects of caffeine ingestion before a resistance exercise session on markers of muscle damage (CK, LDH, ALT, AST) and leukocyte levels. Methods: Fifteen soccer athletes completed two resistance exercise sessions that differed only in the ingestion of caffeine or a placebo preworkout. Results: CK concentration increased significantly following the caffeine session (415.8 ± 62.8 to 542.0 ± 73.5) and the placebo session (411.5 ± 43.3 to 545.8± 59.9), with no significant differences between sessions. Similarly, LDH concentration increased significantly following the caffeine session (377.5 ± 18.0 to 580.5 ± 36.1) and the placebo session (384.8 ± 13.9 to 570.4 ± 36.1), with no significant differences between sessions. Both sessions resulted in significant increases in the total leukocyte count (caffeine = 6.24 ± 2.08 to 8.84 ± 3.41; placebo = 6.36 ± 2.34 to 8.77 ± 3.20), neutrophils (caffeine = 3.37 ± 0.13 to 5.15 ± 0.28; placebo = 3.46 ± 0.17 to 5.12 ± 0.24), lymphocytes (caffeine = 2.19 ± 0.091 to 2.78 ± 0.10; placebo = 2.17 ± 0.100 to 2.75 ± 0.11), and monocytes (caffeine = 0.53 ± 0.02 to 0.72 ± 0.06; placebo = 0.56 ± 0.03 to 0.69 ± 0.04), with no significant differences between sessions. Conclusion: Ingestion of caffeine at 4.5 mg/kg did not augment markers of muscle damage or leukocyte levels above that which occurs through resistance exercise alone.